DESIGN AND HYDRODYNAMIC ANALYSIS OF HORIZONTAL-AXIS HYDROKINETIC TURBINES WITH THREE DIFFERENT HYDROFOILS BY CFD - Betancur, Juan Diego; Ardila Marin, Juan Gonzalo; Chica Arrieta, Edwin Lenin (Journal of Applied Engineering Science, 2020)
The generation of electrical energy using only the movement of water has gained importance in recent years due to its low environmental and social impact. Some of the most used turbines for the extraction of energy by this means are the horizontal axis hydrokinetics, being an emerging technology more studies are required to improve the understanding and functioning of these devices. In this context, the hydrodynamic study to obtain the characteristic curves of the turbines are fundamental. This article presents the design and hydrodynamic analysis for three horizontal axis tri-blade hydrokinetic turbine rotors with commercial profiles (NACA 4412, EPPLER E817, and NRELS802). The Blade Element Momentum (BEM) was used to design three rotors. These geometries were exported to the ANSYS® program where two control volumes were built, which were discretized until the mesh independence was achieved, to guarantee that the results of the simulation do not depend on the discretization of the control volume. The computational fluid dynamics (CFD) were used to observe the behavior of the fluid by varying the speed of rotation of the turbines from 0.1 rad s-1 to 40 rad s-1, obtaining a power coefficient of 0.390 to 0.435. Equivalent to higher powers of 105W. Also, it is evident that for the same conditions the rotor designed with the EPPLER E817 profile presents better performance than built with the NACA4412 and NREL S802.
Keywords: BEM methodology; Hydraulic energy; Hydrokinetic energy; Renewable energy; Simulation